Engagement report on participation in SUN CSA meetings and related meetings with nutrition platforms in 2022 - Duong Thi Thanh; Huynh Thi Thanh Tuyen (Bioversity International and the International Center for Tropical Agriculture, 2022)
The CGIAR Initiative on Asian Mega-Deltas’ Work Package 2 (WP2) researchers from the Alliance Bioversity and CIAT engaged with a wide range of stakeholders in relevant nutrition platforms, including The Technical Working Group on Nutrition (TWGN) and Scaling Up Nutrition Civil Society Alliance (SUN CSA). The purpose of the engagement is to explore partnerships promote co-learning, and share information for WP2 on Nutrition-sensitive Agri-food systems. These activities will help mainstream the nutrition-sensitive approach to the current activities of relevant nutrition platforms in Vietnam.